Revenge of the aesthetic : the place of literature in theory today - Clark, Michael P. (University of California Press, 2000)
This cutting-edge collection of essays showcases the work of some of the most influential theorists of the past thirty years as they grapple with the question of how literature should be treated in contemporary theory. The contributors challenge trends that have recently dominated the field--especially those that emphasize social and political issues over close reading and other analytic methods traditionally associated with literary criticism. Written especially for this collection, these essays argue for the importance of aesthetics, poetics, and aesthetic theory as they present new and stimulating perspectives on the directions which theory and criticism will take in the future.